THE IMPACTS OF BRAND EXPERIENCES ON BRAND LOVE, BRAND TRUST, AND BRAND LOYALTY: AN EMPIRICAL STUDY - Sharon Madeline; Sabrina O. Sihombing (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
Previous studies that studied brand relationships tended to ignore the relationship between brand experience and brand loyalty and the role of brand love and brand trust. Therefore, the main objective of this study is to examine the effect of brand experience on brand loyalty through brand love and brand trust. For this study, questionnaires were distributed via personal and email, with 300 respondents aged between 18 and 50 using a purposive sampling method. Data were analyzed using structural equation modeling. The results found that brand experience has positive brand love and trust, brand love and brand trust have a positive effect on brand loyalty.